Impacts of chilling at the tillering phases on rice growth and grain yield in Northeast China. (27th April 2022) - Guo, Erjing; Wang, Lizhi; Jiang, Shukun; Xiang, Hongtao; Shi, Yanying; Chen, Xi; Cheng, Xue; Wang, Xiaoyu; Zhang, Tianyi; Wang, Lianmin; Feng, Yanjiang; Lai, Yongcai; et al.
Abstract: Chilling is a major constraint on rice production in mountainous regions of the tropics and in the temperate rice‐growing zones of the world. In this study, our goal is to quantify the impacts of chilling at the tillering phases on rice growth and grain yield. In 2017 and 2018, we conducted a factorial chilling treatment at four temperatures (T1, T2, T3 and T4) and four duration days (D2, D4, D6 and D8) on rice plants at the early, middle and late tillering phases. The results showed that chilling at the tillering phases delayed rice growth period. The rice grain yield slightly increased with decrease in chilling temperature but significantly decreased with increase in chilling duration at the tillering phases. For the chilling treatment at T1 (lowest temperature), the D2 (shortest duration) had positive effects on rice yield, while the D8 (longest duration) had adverse effects on rice yield. The middle and late tillering phases were the critical growth phases for rice spike numbers formation, with the increase in temperature and duration, the rice spike numbers per plant significantly decreased. The decrease in chilling temperature and increase in chilling duration both decreased rice thousand‐grain weight under chilling treatments at tillering phases. The prolongation of days from emergence to flowering led to increase in rice aboveground biomass per plant and allocation index of stem; however, the decrease in days from flowering to maturity led to reduction in allocation index of panicle and grain yield under chilling treatments at tillering phases. This study could help farmers to better understand the impacts of chilling on rice growth and yield, especially for rice that are prone to chilling.